Neuropsychological assessment of visual selective attention and processing capacity with head-mounted displays - Foerster, Rebecca M; Poth, Christian H; Behler, Christian; Botsch, Mario; Schneider, Werner X (Neuropsychology, 2019)
Neuropsychological patients often suffer from impairments in visual selective attention and processing capacity components. Their assessment demands a high standardization of testing conditions, which is difficult to achieve across institutions. Head-mounted displays (HMDs) provide a solution. These virtual reality devices cover the entire visual field in a shielded way and thus keep visual stimulation constant. For neuropsychological assessment with HMDs, sufficient reliability is required. We have previously demonstrated that an early developer version of an HMD can be used to reliably measure components of visual processing capacity. However, it is unclear whether this also holds for the assessment of components of visual selective attention. Moreover, it has yet to be established whether now commercially available HMDs are capable of reliable neuropsychological assessment. We assessed the test-retest reliabilities of several components of visual selective attention and processing capacity of healthy subjects with the commercially available HTC Vive. Using an assessment procedure (combiTVA) derived from the theory of visual attention (TVA; Bundesen, 1990), we measured attentional selectivity, lateral bias, processing speed, visual working memory capacity, and the threshold of conscious perception. We compared the reliabilities of these components measured with the HTC Vive with those of a cathode ray tube (CRT) screen, the gold standard of visual presentation in the laboratory. Both devices provided comparable reliabilities. Thus, HMDs fulfill the requirement to replace standard screens. With their inherent visual standardization and portability, they offer unprecedented opportunities for neuropsychological assessment, such as computerized bedside testing and comparisons of test values across institutions. (PsycINFO Database Record (c) 2019 APA, all rights reserved).